2020
DOI: 10.1186/s40560-020-00449-0
|View full text |Cite|
|
Sign up to set email alerts
|

Low-chloride- versus high-chloride-containing hypertonic solution for the treatment of subarachnoid hemorrhage–related complications: The ACETatE (A low ChloriE hyperTonic solution for brain Edema) randomized trial

Abstract: Background Recent reports have demonstrated that among patients with subarachnoid hemorrhage (SAH) treated with hypertonic NaCl, resultant hyperchloremia has been associated with the development of acute kidney injury (AKI). We report a trial comparing the effect of two hypertonic solutions with different chloride contents on the resultant serum chloride concentrations in SAH patients, with a primary outcome aimed at limiting chloride elevation. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…Intracranial hypertension, osmotic therapy, and vasopressor therapy are known to be risk factors of AKI after subarachnoid hemorrhage [2]. But in Sadan et al's study [1], we do not know how many patients received vasopressor therapy before and after randomization in each group. Likewise, before randomization, did the patients receive the same amount of hypertonic solution, and was intravenous chloride load similar in each group?…”
Section: Dear Sirmentioning
confidence: 97%
See 1 more Smart Citation
“…Intracranial hypertension, osmotic therapy, and vasopressor therapy are known to be risk factors of AKI after subarachnoid hemorrhage [2]. But in Sadan et al's study [1], we do not know how many patients received vasopressor therapy before and after randomization in each group. Likewise, before randomization, did the patients receive the same amount of hypertonic solution, and was intravenous chloride load similar in each group?…”
Section: Dear Sirmentioning
confidence: 97%
“…We were interested in the article written by Sadan et al [ 1 ]. After aneurysmal subarachnoid hemorrhage, the authors found an increase in acute kidney injury (AKI) for patients receiving high-chloride versus low-chloride containing a hypertonic solution.…”
mentioning
confidence: 99%
“…We appreciate the interest in our manuscript [1], and the opportunity to respond to the comments. There is no doubt that our study suffers from several shortcomings.…”
Section: To the Editormentioning
confidence: 99%
“…AKI after TBI has been reported developing in 7.6% to 23% patients and is correlated with mortality, functional outcome and length of hospital stay in TBI patients [4][5][6][7]. Mechanisms involved in development of AKI after TBI are diversified, which included systemic inflammation response, neuroendocrine hormone release, hypoperfusion and iatrogenic factors such as blood transfusion, drugs reducing intracranial pressure and usage of nephrotoxic antibiotics [8][9][10][11]. In view of the unfavorable outcome caused by AKI, exploring novel and available biomarkers to predict the possible occurrence of AKI in early stage and consequently avoid medical treatments adverse to normal renal function is beneficial for outcome and recovery of TBI patients.…”
Section: Introductionmentioning
confidence: 99%